Trend of Drug Utilization among Children with Acute Gastroenteritis in a Tertiary Hospital, Edo State, Nigeria - Osarenmwinda, Monday Ikponmwosa; Odama, Ruth Bose (Indian Journal of Pharmacy Practice)
Background: Inappropriate drug utilization is common in clinical practice with a consequent significant negative clinical burden. This study assessed the drug treatment practices for Acute Gastroenteritis (AGE) among under-five children in a tertiary hospital in south-south Nigeria. Materials and Methods: A retrospective cross-sectional study was carried out using prescription records from October 2020 to October 2022; Data was collected using a modified data collection form from World Health Organization (WHO) prescribing indicators, adapted for children’s healthcare. A total of 121 prescriptions met the inclusion criteria. Demographic and clinical characteristics, diagnosis, drugs prescribed, and comorbidity of the patients were extracted from the patient’s folder. Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 22. The analysis was mainly descriptive. Pearson’s chi-squared test was carried out to determine the association of patient characteristics with diagnosis. Statistical significance was set at a p-value is <0.05. Results: Most (56.2%) of the children were males, the age, breastfeeding pattern, and source of drinking water were significantly associated with acute gastroenteritis (p<0.05). A total number of 538 medications were prescribed. The average number of drugs per prescription was 4.25±1.19. Zinc tablets (21.4%) and ORS (21.4%) were the most prescribed drugs, followed by flora-norm (19.9%), 43% of drugs were prescribed by generic name and 38% of patients had co-morbidity. Conclusion: A high level of polypharmacy was observed in this study, age, breastfeeding pattern and sources of drinking water were major associated factors with gastroenteritis. Good hygiene and nutritional practices are thereby recommended to children’s caregivers.
Keywords: Gastroenteritis; Diarrhea; Prescribing pattern; Drug utilization; Children